Phase change-induced tunable dielectric permittivity of poly(vinylidene fluoride)/polyethylene glycol/graphene oxide composites. (15th September 2019) - Tu, Junyang; Li, Hairong; Cai, Ziqing; Zhang, Jingjing; Hu, Xiang; Huang, Jing; Xiong, Chuanxi; Jiang, Ming; Huang, Leping
Abstract: Temperature responsive dielectrics provide the opportunity to obtain permittivity tunable materials, which is particularly useful in modern electrical and electronic devices. However, the applications of the tunable dielectric materials are largely limited owing to the low dielectric transition temperature and/or insufficient shape stability during phase transition. Herein we present the first example of poly(vinylidene fluoride)/polyethylene glycol/graphene oxide (PVDF/PEG/GO) composites with tunable dielectric permittivity based on temperature-dependent phase transition of PEG. The permittivity switching of shape-stabilized PVDF/PEG/GO composites can be triggered above room temperature. This report may provide a roadmap of fabricating new tunable or switchable dielectrics with relatively high dielectric transition temperatures based on polar organic phase change materials.